Analisis Kesulitan Belajar Matematika pada Materi Operasi Hitung Perkalian dan Pembagian di Kelas 3 SD Negeri UPT 023 Pandau Jaya: Penelitian - Masroito; Siti Quratul Ain (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze difficulties in learning mathematics in multiplication and division in grade III B of SD UPT 023 Pandau Jaya. The research method used is qualitative with a case study approach and descriptive design. The research subjects consist of grade III B students, homeroom teachers, and parents selected through purposive sampling. Data were collected through interviews, observations, and documentation, then analyzed using qualitative descriptive methods with data validity testing employing triangulation of sources, techniques, and time. The results of the study indicate that most students still experience weaknesses in arithmetic, lack understanding of basic multiplication and division concepts, and have low motivation to learn. These difficulties are caused by weak mastery of concepts since lower grades, insufficient arithmetic practice at home and at school, unvaried teaching methods, and low learning support from parents. Additionally, students tend to memorize procedures without understanding the meaning of the concepts, making it difficult for them to apply them to word problems or different contexts. These findings highlight the need for learning that emphasizes comprehensive conceptual understanding, the use of interactive and contextual methods, and active parental involvement to improve students' mathematics learning outcomes.